Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1002/adem.201400273
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Effect of High‐Energy Electropulsing on the Phase Transition and Mechanical Properties of Two‐Phase Titanium Alloy Strips

Abstract: The effect of high-energy electropulsing treatment (EPT) on the phase transition and mechanical properties of the two-phase Ti-6Al-4V alloy strips (in the solid solution state) was studied with the help of uniaxial tensile machine, X-ray diffraction, optical stereo-microscope, scanning electron microscope, and electrical resistance meters. Results show that the ductility of the titanium alloy strips under EPT could be enhanced remarkably at most by 225% while keeping the tensile strength nearly unchanged. EPT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Ye et al revealed that the precipitated β-Ti from Ti-6Al-4V (α + β) alloy gathered and formed continuous strips and migrated from inside worm-like particles to an equiaxed grain area after EPT in a very short duration, for which it was assumed that the nucleation rate of the phase transition α → β was accelerated [ 80 ]. Song et al reported that fine and uniform grains with a size of 30–50 μm of as-cast TiAl alloys could be obtained from the original coarse lamellar grains of about 1000 μm by EPT.…”
Section: Effects Of Ept On Microstructure and Texturementioning
confidence: 99%
“…Ye et al revealed that the precipitated β-Ti from Ti-6Al-4V (α + β) alloy gathered and formed continuous strips and migrated from inside worm-like particles to an equiaxed grain area after EPT in a very short duration, for which it was assumed that the nucleation rate of the phase transition α → β was accelerated [ 80 ]. Song et al reported that fine and uniform grains with a size of 30–50 μm of as-cast TiAl alloys could be obtained from the original coarse lamellar grains of about 1000 μm by EPT.…”
Section: Effects Of Ept On Microstructure and Texturementioning
confidence: 99%
“…As we known, the strengthening mechanism of materials mainly contains solid solution strengthening and alloying, transformation hardening, grain boundary strengthening, and precipitation strengthening . In the crystallization treatment, there was no change in the chemical composition of RT330 enamel substrate.…”
Section: Resultsmentioning
confidence: 98%
“…Li X [9] found that the titanium alloy surface columnar dendrites is breaked and drive equiaxed crystal migration under the combined action of the skin effect and Lorentz force. Ye X [10] have studied the effect of pulse current on the microstructure, mechanical properties and corrosion properties of Ti6Al4V alloy in recent years. Relevant literature shows [11][12] that the external magnetic field has an impact on the microstructure and properties of titanium alloy during the heat treatment.…”
Section: Introductionmentioning
confidence: 99%